Effect of Adding Various Organic Acids During the Feed Withdrawal Period on Salmonella Reduction in Broilers - Abdullah , Faten K.; Al-Nasser, Afaf Y.; Al-Zenki, Sameer F.; Al-Saffar, Abdulameer E.; Al-Bahouh, Mariam E.; Mashaly, Magdy (International Journal of Poultry Science, 2012)
Salmonella contamination of broilers is a major problem that faces the poultry industry in Kuwait and elsewhere since it affects the consumption of poultry meat. Therefore, utilization of different control measures leading to the reduction of Salmonella contamination is an important task for the broiler industry and the public health authorities in Kuwait. An important strategy is to significantly reduce the levels of Salmonella at the farm level and improve the manufacturing practices in the processing plant to prevent the risk of cross contamination. In our Department, different treatments have been used to control the contamination of this pathogen at the farm level, one of which is presented in the current study. The objective of the current study is to determine the effect of using different organic acids in the drinking water during the feed withdrawal period on reducing Salmonella in broilers. One hundred and twenty broiler chicks were originally housed in each of 36 floor pens. At the time of feed withdrawal, the pens were divided into four groups of nine pens each and were used for one of four treatments. These treatments included the control group and received untreated water, the second group received water containing 0.1% acetic acid, the third group received water containing 0.1% formic acid and the fourth group received water containing 0.1% lactic acid for a period of eight hrs. This study was repeated both in the summer and winter seasons. The prevalence of Salmonella on the chicken body, ceca and in the crop was determined before and post treatment at the farm and then at the processing plant. In addition to reducing body Salmonella contamination significantly (p<0.05) post treatment at the farm, in both seasons, it was found that acid treatments, in the summer season, significantly (p<0.05) reduced Salmonella contamination in the carcass at the processing plant from 36% (control) to 16, 13, 13% for acetic, formic and lactic acid treatments, respectively. In the winter season, both formic and lactic acid treatments reduced Salmonella contamination in the carcass at the processing plant and the reduction was significant (p<0.05) for formic acid treatment. It can be concluded that using organic acids in the water during the feed withdrawal period, both in the summer and winter seasons, can be beneficiary in reducing broiler Salmonella contamination both at the farm and at the processing plant.